Time - Goudsmit, Samuel Abraham 1902-; Claiborne, Robert (New York Time-Life, 1969)
A comprehensive exploration into the many facets of time. Examines through text and photograph the concepts of measurement and use of timekeeping instruments in astronomy, physics, engineering, geology and biology.
Bibliography: p. 196.
Keywords: Time; Time